Long-term Death Rates, West Nile Virus Epidemic, Israel, 2000 - Green, Manfred S. (Centers for Disease Control and Prevention, 2005)
We studied the 2-year death rate of 246 adults discharged from hospital after experiencing acute West Nile Virus infection in Israel during 2000. The age- and sex-adjusted death rates were significantly higher than in the general population. This excess was greater for men. Significant adverse prognostic factors were age, male sex, diabetes mellitus, and dementia.